Role Of Stress To Quitting Intention Between Men And Women Employees In Hotel Industry - Isanawikrama, Isanawikrama; Hutomo, Edwin Joyo; Buana, Yud (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The attitudes and behaviors of employees who provide frontline service and address the extent to which relationships vary among male and female employees. The overall model predicts effects of role stress and work or no work conflict on customer-contact employees’ job performance, job, and life satisfaction, and quitting intent. Results of structural equations modeling suggest an important role for work/no work conflict overall as well as two areas of interesting variation across gender. Specifically, multisampling structural equations analyses suggest that role stress affects female service provider’s job performance more negatively than it does males’, and that job satisfaction is related more highly to quitting intent among males. Overall, results suggest interesting similarities and differences across gender.